Defending the realm? : The politics of Britain's small wars since 1945 - Edwards, Aaron (Book collections on Project MUSE., 2012)
This book details the tactical and operational dynamics of Britain's small wars, arguing that the military's use of force was more heavily constrained by wider strategic and political considerations than previously admitted.